Exploring the Coronal Magnetic Field with Galactic Cosmic Rays: The Sun Shadow Observed by HAWC - R. Alfaro; C. Alvarez; J. C. Arteaga-Velázquez; K. P. Arunbabu; D. Avila Rojas; R. Babu; E. Belmont-Moreno; K. S. Caballero-Mora; T. Capistrán; A. Carramiñana; S. Casanova; P. Colín-Farias; et al. (The Astrophysical Journal, 2024)
Galactic cosmic rays (GCRs) are charged particles that reach the heliosphere almost isotropically in a wide energy range. In the inner heliosphere, the GCR flux is modulated by solar activity so that only energetic GCRs reach the lower layers of the solar atmosphere. In this work, we propose that high-energy GCRs can be used to explore the solar magnetic fields at low coronal altitudes. We used GCR data collected by the High-Altitude Water Cherenkov observatory to construct maps of GCR flux coming from the Sun’s sky direction and studied the observed GCR deficit, known as Sun shadow (SS), over a 6 yr period (2016–2021) with a time cadence of 27.3 days. We confirm that the SS is correlated with sunspot number, but we focus on the relationship between the photospheric solar magnetic field measured at different heliolatitudes and the relative GCR deficit at different energies. We found a linear relationship between the relative deficit of GCRs represented by the depth of the SS and the solar magnetic field. This relationship is evident in the observed energy range of 2.5–226 TeV, but is strongest in the range of 12.4 33.4 TeV, which implies that this is the best energy range to study the evolution of magnetic fields in the low solar atmosphere.